Fukugoudoushi dalam Novel Suzume no Tojimari - Alfian, Muhammad; Prihandari, Ismi; Efrizal; Zuliastutik, Hendri (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2024)
This reasearch discusses the structure of fukugoudoushi formation based on the word classes that form it and the meaning relationships arising from the combination of word classes that form the fukugoudoushi. Both problems are analyzed using the theory of Himeno in Nohejl (2016) and the theory of fukugoudoushi forming meaning relationships of Himeno in Hayashi (1993). The method used is narrative qualitative, which discusses the meaning of fukugoudoushi seen in the novel Suzume no Tojimari with narrative chronology. The result of this research found 57 data points for verb and verb pattern (V1+V2). In addition, there are 9 data points having a V1 relationship as the determinant of overall meaning, 32 data points having a V1 relationship followed by a V2, and 13 data points having a V2 relationship that can only be expressed in other words, 3 data points having a V1 and V2 meaning relationship when combined becomes difficult to analyze. Keywords: fukugoudoushi; morphology; novel; Suzume no Tojimari.